The effect of double-row wing bag sand barrier on wind prevention and sand fixation: wind tunnel simulation and field verification - Han, Xue-Ying; Yang, Wen-Bin; Gao, Tian-Xiao; Jia, Guang-Pu; Liu, Jing (Frontiers in Earth Science, 2023)
Most of the sand fixation technologies utilized locally and internationally are static or dynamic, making it challenging for a single sand fixation mode to function in a harsh environment. Therefore, the development of a sand fixation mode that combines resistance and consolidation has emerged as a trending topic in sand control research. Our team developed the wing bag sand barrier, which is a static and dynamic combination of sand fixation mode. In this study, we examined the characteristics of airflow velocity field and sand resistance near double-row wing bag sand barrier under different wind conditions to screen out the optimal mode of wing bag sand barrier. The analyses were conducted under nine configuration modes through the wind tunnel simulation experiment and the field experiment. The inflection point of the airflow was always 5H on the windward side of the wing bag sand barrier, regardless of the wind speed. The protection range of the wing bag sand barrier with the same specifications was gradually weakened with the increase of the wind speed. However, there was an upward trend in both total sand accumulation and sand accumulation of each height layer. When the wind speed was slower than 8 m/s, the sand accumulation behind the barrier was mainly concentrated in the 0-10 cm height layer, and when the wind speed was 12 m/s, it was mainly concentrated in the 30-60 cm height layer. At the leeward side of the wing bag sand barrier, sand particles were rejected in the range of 0-30 cm; however, they were conducted in the range of 30-60 cm. The protective effect of the wing bag sand barrier simulated in the wind tunnel experiment was consistent with that of the field experiment. For a wind speed of slower than 6 m/s, the recommended specification for the field-installed wing bag sand barrier was 25×20 cm or 30×20 cm. The specifications 25×20 cm and 25×25 cm were recommended at an inlet wind speed of 8 m/s. When the wind speed was greater than 12 m/s, the recommended specifications were 25×25 cm, 25×20 cm, and 20×25 cm.